Metallic Embroidery and Masters of Thread-Breaking as an Example of Cultural Heritage in Turkish Handicrafts - Er, Harun; Gürel, Davut (Journal of History Culture and Art Research, 2020)
One of the most important elements that give the insight to ensure identity and dimension to the societies is the tradition of handicrafts. These valuable traditions, which have been inherited from generation to generation until today, are now on the verge of extinction because of globalization and developments in production technologies. Local, national and international precautions have been taken by today’s societies to sustain and protect these valuable traditions. The purpose of this study is to analyze the past, present, and future of the art of thread-breaking (a specific type of metallic embroidery named ‘Bartın işi’) which is one of the valuable Turkish traditional handicrafts. For this purpose, five embroidery masters who perform this traditional art were interviewed with semi-structural interview forms. According to the findings obtained through these processes: Metallic embroidery masters learnt this art out of curiosity with internal motivation, they performed this art within the frame of neighborhood culture, the art is usually learnt through observations and trial-and-error processes rather than master-apprentice relationship and there have been changes over time in the variety of the instruments and motifs used in the making of these embroideries and the areas of use. On the other hand, it was observed that the art of metallic embroidery has been mostly performed by individuals over middle age and today the young show little interest in this art. Participants of the study emphasized that it is necessary to support and increase the local and international advertising and educational activities to popularize this valuable art tradition.